Coronary heart disease knowledge and risk factors among Filipino-Americans connected to primary care services - Angosta, Alona N. Dalusong (ProQuest LLC, 2011)
Coronary heart disease (CHD) is the leading cause of death of Filipino-Americans (FAs). Despite the growing numbers of FAs in the United States, little is known about their CHD knowledge and risk factors. The purposes of this study were to examine the baseline knowledge and risk factors of CHD among FAs and to describe the relationships between knowledge, sociodemographic, and socioeconomic characteristic variables of FAs between the ages of 35-75 years. The study sample consisted of 120 FAs (N = 120) who were connected to primary care services. Data were collected from three primary care clinics in Las Vegas, Nevada between the months of May and July, 2010. Participants completed the Demographics and the Heart Disease Fact Questionnaire (HDFQ) forms on CHD knowledge and CHD risk factors. Descriptive statistics, item response frequencies, and t-tests revealed most Fas were knowledgeable about CHD. The mean CHD knowledge scores of the sample was 15.8 (SD = 4.26) out of the 21 CHD knowledge total score points. When knowledge scores were compared between men and women, women had higher CHD knowledge scores than men (t = 2.438, p = .016). Descriptive statistics and item response frequencies also revealed FAs were at an increased risk of CHD. Many of them had CHD risk factors: Lack of exercise (65.8%), hypertension (50%), dyslipidemia (36.7%), abdominal adiposity (27.5%), Diabetes Mellitus Type 2 (25%), overweight (22.5%), and smoking (10%). Gender, education, and income were significantly correlated with CHD knowledge, however, gender (b = .190, t = 2.21, p = .029) and education (b = .256, t =2.85, p = .005) were the best predictors of CHD knowledge. CHD risk factors are highly prevalent among FAs. Implications for practice should focus on primary and secondary preventions. Further research is warranted to explore the impact of health behavior, culture, sociodemographic/socioeconomic factors on CHD.